Preclinical Studies of the Off-Target Reactivity of AFP158-Specific TCR Engineered T Cells - Cai, Lun; Caraballo Galva, Leidy D.; Peng, Yibing; Luo, Xiaobing; Zhu, Wei; Yao, Yihong; Ji, Yun; He, Yukai (Frontiers in Immunology, 2020)
Autologous T cells engineered with T receptor genes (TCR) are being studied to treat cancers. We have recently identified a panel of mouse TCRs specific for the HLA-A0201/alpha fetoprotein epitope (AFP158) complex and have shown that human T cells engineered with these TCR genes (TCR-Ts) can eradicate hepatocellular carcinoma xenografts in NSG mice. However, due to TCR’s promiscuity, their off-target cross-reactivity must be studied prior to conducting clinical trials. In this study, we conducted in vitro X-scan assay and in silico analysis to determine the off-target cross-reactivity of 3 AFP158-specific TCR-Ts. We found that the 3 AFP158-specific TCR-Ts could be cross-activated by ENPP1436 peptide and that the TCR3-Ts could also be activated by another off-target peptide, RCL1215. However, compared to AFP158, it requires 250 times more ENPP1436 and 10,000 times more RCL1215 peptides to achieve the same level of activation. The EC50 of ENPP1436 peptide for activating TCR-Ts is approximately 17-33 times higher than AFP158. Importantly, the ENPP1+ tumor cells did not activate TCR1-Ts and TCR2-Ts, and only weakly activated TCR3-Ts. The IFNγ produced by TCR3-Ts after ENPP1+ cell stimulation was >22x lower than that after HepG2 cells. And, all TCR-Ts did not kill ENPP1+ tumor cells. Furthermore, ectopic over-expression of ENPP1 protein in HLA-A2+ tumor cells did not activate TCR-Ts. In silico analysis showed that the ENPP1436 peptide affinity for HLA-A0201 was ranked 40 times lower than AFP158 and the chance of ENPP1436 peptide being processed and presented by HLA-A0201 was 100 times less likely than AFP158. In contrast, the two off-targets (Titin and MAGE-A3) that did cause severe toxicity in previous trials have the same or higher MHC-binding affinity and the same or higher chance of being processed and presented. In conclusion, our data shows that TCR-Ts can be activated by off-target ENPP1436 peptide. But, compared to target AFP158, it requires at least 250 times more ENPP1436 to achieve the same level of activation. Importantly, ENPP1436 peptide in human cells is not processed and presented to a sufficient level to activate the AFP158-specific TCR-Ts. Thus, these TCR-Ts, especially the TCR1-Ts and TCR2-Ts, will unlikely cause significant off-target toxicity.